Labor market and public employment and income policies (Research, Society and Development, 2020)
The objective of this paper was to analyze the main labor market indicators involving commercial companies and service providers and public employment and qualification policies in a municipality in the interior of the state of Paraná. With a mixed methods approach, data were collected through semi-structured interviews and the application of questionnaires, in addition to the analysis of social indicators. Four agencies were researched that could be involved in public policies for job creation and 100 workers who attend the city worker agency. In relation to the agencies, the strong performance of the Entrepreneur Agency, the SETI Good Business Program in partnership with the University, and the Worker Agency in partnership with other institutions for qualification were noted. Results showed that in Guarapuava the set of public policies is still incipient in the sense of improving qualification and expanding employability.